2011
DOI: 10.1007/s12562-011-0334-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calorie restriction on the expression of manganese superoxide dismutase and catalase under oxidative stress conditions in the rotifer Brachionus plicatilis

Abstract: Calorie restriction (CR) in the rotifer Brachionus plicatilis extends its lifespan, as it enhances the expression of antioxidant enzymes such as manganese superoxide dismutase (Mn SOD) and catalase. Here we show that CR also increased the mRNA levels of these antioxidant enzymes upon exposure to oxidative stress. Rotifers cultured under CR showed a higher survival rate than those fed ad libitum (AL) upon exposure to 0.05-0.2 lM juglone, an oxidative stress inducer. The relative mRNA levels of Mn SOD and catala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…In fact, overexpression of hsp22 has been shown to increase fly lifespan, protect flies against paraquat, and improve their locomotor ability (Morrow et al 2004). In rotifers, DR pretreatment was reported to benefit paraquat and juglone tolerance (Kailasam et al 2011;Ozaki et al 2010). A previous study indicated that the beneficial effects of DR may contribute to the improvement in antioxidant gene expression (SOD and CAT) (Yang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, overexpression of hsp22 has been shown to increase fly lifespan, protect flies against paraquat, and improve their locomotor ability (Morrow et al 2004). In rotifers, DR pretreatment was reported to benefit paraquat and juglone tolerance (Kailasam et al 2011;Ozaki et al 2010). A previous study indicated that the beneficial effects of DR may contribute to the improvement in antioxidant gene expression (SOD and CAT) (Yang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…after 24 h exposure (Kailasam et al, 2011;Kim et al, 2011;Rhee et al, 2012). The test was conducted in triplicate and the results were presented as lethal concentrations (LC 10 and LC 50 ) observing 10 and 50% of mortality, respectively (Finney, 1971).…”
Section: Genementioning
confidence: 99%
“…In the laboratory, DR is one of the most commonly used life-history alterations among evolutionarily distinct eukaryotes, from single-cell to multicellular organisms [16]–[19]. Previous studies have suggested that DR can extend the lifespan of rotifers and enhance their resistance to oxidative stress [20][24]. Interestingly, DR-induced longevity and other beneficial effects of DR can transmit to the next generation in rotifers [25].…”
Section: Introductionmentioning
confidence: 99%